Overexpression of Myo1e in Mouse Podocytes Enhances Cellular Endocytosis, Migration, and Adhesion. Issue 2 (February 2014) - Jin, Xia; Wang, Wenjing; Mao, Jianhua; Shen, Huijun; Fu, Haidong; Wang, Xia; Gu, Weizhong; Liu, Aimin; Yu, Huimin; Shu, Qiang; Du, Lizhong
ABSTRACT Podocytes are a terminally differentiated and highly specialized cell type in the glomerulus that forms a crucial component of the glomerular filtration barrier. Recently, Myo1e was identified in the podocytes of glomeruli. Myo1e podocyte‐specific knockout mice exhibit proteinuria, podocyte foot process effacement, glomerular basement membrane disorganization, signs of chronic renal injury, and kidney inflammation. After overexpression of Myo1e in a conditionally immortalized mouse podocyte cell line (MPC5), podocyte migration was evaluated via transwell assay, endocytosis was evaluated using FITC‐transferrin, and adhesion was evaluated using a detachment assay after puromycin aminonucleoside treatment. Myo1e overexpression significantly increased the adherence of podocytes. ANOVA analysis indicated significant differences for cell adhesion between the overexpression and control groups (overexpression vs. control, t = 11.3199, P = 0.005; overexpression vs. negative control, t = 12.0570, P = 0.0006). Overexpression of Myo1e inhibited puromycin aminonucleoside‐induced podocyte detachment, and the number of cells remaining on the bottom of the culture plate increased. Cell migration was enhanced in Myo1e‐overexpressing podocytes in the transwell migration assay. Internalization of FITC‐transferrin also increased in Myo1e‐overexpressing podocytes relative to control cells. Overexpression of Myo1e can enhance podocyte migration ability, endocytosis, and attachment to the glomerular basement membrane. Restoration of Myo1e expression in podocytes may therefore strengthen their functional integrity against environmental and mechanical injury. J. Cell. Biochem. 115: 410–419, 2014. © 2013 Wiley Periodicals, Inc.